DETERMINATION OF RELATIVE INFLUENCE OF IMPORTANT FACTORS ON THE ACCEPTANCE OF MOBILE COMMERCE USING NEURAL NETWORK APPROACH - Kalinić, Zoran S; Marinković, Veljko (Poslovna ekonomija, 2017)
The wide spread of mobile devices has led to the development of commercial applications and services, and today more and more people use their mobile phone for the purchase of goods and services or mobile payments. When introducing any new technology it is important to determine the factors that significantly influence the consumer’s decision to begin to use it. The paper presents the determination of the relative impact of factors on the acceptance of mobile commerce in our country. Study uses extended TAM model and artificial neural networks, which allow the modeling of nonlinear relationship between variables. Perceived usefulness was identified as the most influential factor on the intention to use mobile commerce, while as the most influential factor on the perceived usefulness study identifies customization. Finally, research has shown that the greatest impact on the ease of use perceived by mobile commerce consumers has factor of mobility, followed by customization.